Qualification of a system technology for selective laser-based quasi-simultaneous soldering with an integrated pyrometric process control - Ermer, Jakob; Saffer, Judith; Schaumberger, Kerstin; Kaufmann, Florian; Wittmann, Alexander; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2020)
Due to the tendency of miniaturization of electronic components, the increased use of thermally sensitive circuit boards e.g. LCDs, a large number of requirements arises for a selective laser beam soldering process. To enhance the possibilities of selective soldering, a system technology for quasi-simultaneous, pyrometric controlled laser soldering was qualified. The systems capability is to enable a controlled laser soldering process at different spot-sizes, varying electronic device layouts and different irradiation strategies. An inline emission measurement via pyrometer gains live-data from the soldering process, evaluates them and transfers them in a closed loop cycle to the laser power control. To enable a process control over a large scanning field, a chromatic corrected f-theta optic, which compensates the chromatic aberration between laser and pyrometer wavelength was used. Different scanning strategies and varying laser power profiles have been evaluated regarding their influence on the process quality.<br
Keywords: selective laser soldering; pyrometric process control; microelectronic devices; chromatic corrected f-theta lens; fiber laser